European trends in the development of occupations and qualifications : Volume 1 - Sellin, Burkart [Verfasser] (Office for Official Publications of the European Communities, 1999)
This study is inteded for a wide range of readers who wish to keep up to date with the most important trends in the development of occupations and qualifications in the face of current demographic, social, economic, technical, environmental and cultural changes. The present volume 1 provides a general summary of the most important trends at macro level. "The analyses are based on the findings of interdisciplinary and multidisciplinary research in the field of vocational training and the labour market, on comparative statistics drawn up by the European Statistical Office concerning practically oriented projects within the EU's education and vocational training programme, on the results of transnational studies in the framework of CEDEFOP's thematic research network (Ciretoq), and on findings from the EU-wide socioeconomic research programme in the field of education and vocational training. They stress the urgent need for training and qualification opportunities to be expanded at all levels in all regions of the EU, in respect of all target groups and all age groups, for economic and competitive reasons as well as for reasons of social and educational policy." (Herausgeber, BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; G 1.2.3 Qualifikationsentwicklungen; G 2.3.4 Qualifikationswandel; G 2.3.5 Wirtschaftsstrukturwandel; G 1.2.2.3 Beschäftigungsformen; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; I 2.2 Europa; EU-Bildungspolitik; Berufsbildung; Berufsbildungsforschung; Qualifikationsentwicklung; Qualifikationsanpassung; Strukturwandel; Bildungspolitik; Beschäftigung